Positive Urgency, Drinking Preoccupation, and Alcohol Problems in College Students. (12th May 2022) - Regan, Timothy; Harris, Bethany; McCredie, Morgan; Fields, Sherecce
Abstract: Objective: Individuals high in positive urgency (i.e., impulsiveness stemming from high positive mood) may be more preoccupied with alcohol-related cognitions. Our aim was to examine how positive urgency, drinking preoccupation, and consumption patterns concurrently influence the endorsement of alcohol-related problems. Method: We sampled 756 students enrolled in a large, public U.S. university, who completed a cross-sectional survey online. Their mean age was 19.6 ( SD = 1.72), 71.3% identified as female, and participants largely identified as Caucasian (65.5%) and Hispanic/Latinx (22.1%). Self-report measurements of trait positive urgency and drinking preoccupation and retrospective data of alcohol use and alcohol-related problems were collected. A series of linear regressions tested for a hypothesized indirect effect between variables. Results: We discovered an indirect effect in the relationship between positive urgency and alcohol-related problems via drinking preoccupation. A significant conditional effect showed that this relationship was influenced by past 30-day alcohol consumption, with the effect gaining strength as consumption days increased. Conclusions: Students with high positive urgency may be more engrossed with alcohol-related drinking cognitions, leading to negative consequences as their alcohol consumption increases. This potential association can inform tailored intervention plans for college student alcohol control, such as successfully managing intense positive moods and alcohol-related cognitions and triggers.